Investigating the Influence of Managers’ Androgenic Characteristics on Organizations’ Fulfillment of Social Responsibility: Focus on Data Mining and Data Envelopment Analysis Models - Maleki Chubari, Mojtaba; Rajabi Mohaddam, Zahra (International Journal of Business Management and Entrepreneurship, 2024)
The purpose of this research is to investigate the effect of androgenic characteristics of managers on the way companies fulfill their social responsibilities. To achieve this research goal, we reviewed the data of 143 companies admitted to the Tehran Stock Exchange between 2012 and 2021, which spans nine consecutive years. Then, to examine and analyze the data, we used statistical methods such as regression analysis of combined (panel) data and data mining methods like neural networks and decision trees. We applied Charnes and Cooper’s function (1962) to ascertain corporate social responsibility (CSR). Results suggested that the androgenic characteristics of managers had significant positive effects on fulfilling companies’ social responsibilities. This research was the first to study the androgenic feature as an independent variable associated with managers’ appearance. In other words, in this research, for the first time, a non-financial variable that is related to a person’s appearance has been investigated in relation to the way companies fulfill their CSR.